RAGAM AKTIVITAS SISWA SEKOLAH DASAR KELAS V PADA JAM ISTIRAHAT DI SDN BANYUAJUH 3 - Faiza, Alya Aulia (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to identify and describe the various activities undertaken by fifth-grade students during recess and how they utilize this break time at SDN Banyuajuh 3. The study employs a qualitative approach with a descriptive method. The research subjects consisted of ten fifth-grade students and one fifth-grade teacher acting as a supporting informant. Data were collected through observation, interviews, and documentation, and subsequently analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that fifth-grade students engage in a variety of activities during recess, such as playing with friends, purchasing food or drinks at the canteen, completing assignments, and resting inside the classroom. The most common activity is playing with friends, particularly physical games like soccer and tag. Meanwhile, some students choose to buy snacks or rest in the classroom because they feel hungry or find the classroom environment more comfortable. Students utilize recess to meet physical and social needs, alleviate fatigue and boredom following lessons, and interact with peers. Thus, recess serves not merely as a pause from academic activities but also as an opportunity for students to replenish their energy, engage in preferred activities, and prepare for the next lesson.
Keywords: student activities; recess; elementary school students; use of recess time